Acquired enterovesical fistulas - Barberousse, Carlos; Santiago, Pablo; Rodríguez, Pablo (Cirugía del Uruguay, 2006)
12 patients with acquired enterovesical fistulas during a period between 1990 and 2002 were reviewed., considering etiological aspects, clinical presentation, paraclinical examinations and surgical treatment and comparing them with those in similar published series. Etiology includes diverticular disease (six cases), Crohn’s disease (three cases), radiation injury (one case) and surgical or instrumental iatrogenia (two cases). Specific symptoms and the clinical presentation were related to the causal disease. Paraclinical examinations were analysed. The importance of computerized abdominal tomography is emphatically stressed. Finally, treatment and outcomes were considered. In all cases surgery was performed. The most common procedure (75%) was intestinal resection with primary anastomosis (one-stage resection) and vesical repair. Other procedures were colostomy without resection (16%) and resection without anastomosis (8%). No mortality was registered and the outcome was favourable in all cases. The functional results were better in one-stage resection cases. We concluded that enterovesical fistula is a rare disease. Etiology and relative frequency is similar to those in other published series with the only difference that no neoplastic fistulas were found.. Surgical treatment is effective and one stage resection and anastomosis is recommended if possible because the better functional outcome